2018
DOI: 10.1021/acsomega.8b00608
|View full text |Cite
|
Sign up to set email alerts
|

Nanotoxicity of Silver Nanoparticles on HEK293T Cells: A Combined Study Using Biomechanical and Biological Techniques

Abstract: Human embryonic kidney 293T cells (HEK293T cells) before and after treatment with silver nanoparticles (AgNPs) were measured using advanced atomic force microscopy (AFM) force measurement technique, and the biomechanical property of cells was analyzed using a theoretical model. The biomechanical results showed that the factor of viscosity of untreated HEK293T cells reduced from 0.65 to 0.40 for cells exposure to 40 μg/mL of AgNPs. Comet assay indicated that significant DNA damage occurred in the treated cells,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 41 publications
0
37
0
Order By: Relevance
“…In vitro cytotoxicity studies are often used to characterize the biological response to AgNPs, and the results of these studies may be used to identify hazards associated with exposure to AgNPs. Some important studies that have shown the toxic effects of AgNPs on different cell lines, including macrophages (RAW 264.7), including bronchial epithelial cells (BEAS-2B), alveolar epithelial cells (A549), hepatocytes (C3A, HepG2), colon cells (Caco2), skin keratinocytes (HaCaT), human epidermal keratinocytes (HEKs), erythrocytes, neuroblastoma cells, embryonic kidney cells (HEK293T), porcine kidney cells (Pk 15), monocytic cells (THP-1), and stem cells [20,[108][109][110][111][112][113][114][115][116][117], are discussed below.…”
Section: In Vitro Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro cytotoxicity studies are often used to characterize the biological response to AgNPs, and the results of these studies may be used to identify hazards associated with exposure to AgNPs. Some important studies that have shown the toxic effects of AgNPs on different cell lines, including macrophages (RAW 264.7), including bronchial epithelial cells (BEAS-2B), alveolar epithelial cells (A549), hepatocytes (C3A, HepG2), colon cells (Caco2), skin keratinocytes (HaCaT), human epidermal keratinocytes (HEKs), erythrocytes, neuroblastoma cells, embryonic kidney cells (HEK293T), porcine kidney cells (Pk 15), monocytic cells (THP-1), and stem cells [20,[108][109][110][111][112][113][114][115][116][117], are discussed below.…”
Section: In Vitro Effectsmentioning
confidence: 99%
“…Results of in vitro studies have indicated that AgNPs are toxic to the mammalian cells that are derived from the skin, the liver, the lung, the brain, the vascular system and reproductive organs [144]. The cytotoxicity of AgNPs depends on their size, shape, surface charge, coating/capping agent, dosage, oxidation state, agglomeration and type of pathogens against which their toxicity is investigated [42,108,145,146]. Despite these studies, the toxicological of AgNPs mechanism is still unclear.…”
Section: In Vitro Effectsmentioning
confidence: 99%
“…As recognized, extended exposure to Ag through oral and inhalation can lead to Argyria or Argyrosis, i.e., chronic disorders of skin microvessels and eyes in humans [23,48]. In vitro cell culture studies have indicated toxic effects of AgNPs in immortal human skin keratinocytes (HaCaT), human erythrocytes, human neuroblastoma cells, human embryonic kidney cells (HEK293T), human liver cells (HepG2), and human colon cells (Caco2) [49,50,51,52,53,54,55]. In vivo animal studies have revealed toxic effects of AgNPs in rodents by accumulating in their liver, spleen, and lung [56,57].…”
Section: Introductionmentioning
confidence: 99%
“…In vivo animal studies have revealed toxic effects of AgNPs in rodents by accumulating in their liver, spleen, and lung [56,57]. Similarly, AgNPs-mediated cytotoxicity in mammalian cells [55,58,59,60,61,62] depends greatly on the nanoparticle size, shape, surface charge, dosage, oxidation state, and agglomeration condition as well as the cell type. This article provides a state-of-the-art review on the recent development in the synthesis of AgNPs, their antibacterial activity, and cytotoxic effects in mammalian cells, especially in the past five years.…”
Section: Introductionmentioning
confidence: 99%
“…A strong negative correlation (R 2 = 0.92) between the normalized elastic modulus (to controls) of surviving cells and the percentage of living cells in that environment was noted, suggesting that (a) the health of organelles in a toxic environment strongly influences cell mechanics, (b) cell biomechanics could also be correlated to biochemical outcomes, in addition to biophysical changes, and (c) biomechanical characteristics (modulus, tether forces, adhesion) are key markers and predictors of neurotoxicity. In studies exploring role of silver nanoparticles on human embryonic kidney cells, a similar strong negative correlation between DNA damage and factor of viscosity was noted (Jiang et al 2018). Multivariate logistic regression analysis (Alexopoulos 2010;Kozel et al 2014) suggested that elastic modulus (p < 0.001), adhesion force (p < 0.0001), and tether force (p < 0.0001) were significant predictors of NPC toxicity.…”
Section: Discussionmentioning
confidence: 71%